2023
DOI: 10.3390/rs15071864
|View full text |Cite
|
Sign up to set email alerts
|

Underwater 3D Scanning System for Cultural Heritage Documentation

Abstract: Three-dimensional capturing of underwater archeological sites or sunken shipwrecks can support important documentation purposes. In this study, a novel 3D scanning system based on structured illumination is introduced, which supports cultural heritage documentation and measurement tasks in underwater environments. The newly developed system consists of two monochrome measurement cameras, a projection unit that produces aperiodic sinusoidal fringe patterns, two flashlights, a color camera, an inertial measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The question of the accuracy of the measurements with respect to a ground truth remains. [22] proposes an application of 3D reconstruction for underwater archeology. The system consists of two monochrome cameras and a sinusoidal light pattern projector.…”
Section: Main Methodsmentioning
confidence: 99%
“…The question of the accuracy of the measurements with respect to a ground truth remains. [22] proposes an application of 3D reconstruction for underwater archeology. The system consists of two monochrome cameras and a sinusoidal light pattern projector.…”
Section: Main Methodsmentioning
confidence: 99%
“…The question of the accuracy of the measurements with respect to a ground truth remains. Braeuer-Burchardt et al [ 39 ] proposed an application of 3D reconstruction for underwater archeology. Their system consists of two monochrome cameras and a sinusoidal light pattern projector.…”
Section: Related Workmentioning
confidence: 99%
“…Our team's previous work [5] research found that by combining close-range photogrammetry and structured light technology, combining their respective advantages, there is excellent potential for high-precision measurement of the three-dimensional topography of large objects [1,66,67]. Close-range photogrammetry technology captures high-resolution images from multiple angles, integrates global control points, and can accurately reconstruct the geometric structure of objects.…”
Section: Ahf For Close-range Photogrammetry and Structured Light Fusionmentioning
confidence: 99%